GENRE ANALYSIS OF MINUTES OF MEETINGS CONDUCTED IN ENGLISH BY THAI ENGINEERS - Changpueng, Piyatida; Patpong, Pattama (Indonesian Journal of Applied Linguistics, 2021)
Meetings are one of the common activities that play an important role in the field of business.  For the community of Thai engineers, meetings become the salient aspects of their work, and therefore the effective writing of minutes of meetings is required. As such a writing is essential in the field, analyzing the corpus of the minutes of meetings would shed a light the patterns of meaning instantiated through those minutes.  A corpus of 115 minutes of meetings were collected and analyzed using the genre analysis framework (moves and steps) of Swales (1990), Bhatia (1993), and Thaweewong (2006).  Further, the lexico-grammatical features e.g., tenses and voices instantiated through the meetings were examined. Results of the analysis showed that Thai engineers use e-mail as the medium in writing the minutes in two ways:  using regular e-mail messages (e-mail form) and using the company form. In terms of moves, there were seven common moves observed in the writing of the minutes: (1) the heading; (2) an opening salutation; (3) establishing a correspondence chain; (4) the content of the meeting; (5) a closing correspondence chain; (6) a closing salutation; and (7) attaching a document. In terms of lexicogrammar, there are some prominent features such as the simple present tense, active voice, noun phrases, proper nouns, abbreviations, and key word lists.  The results above can be further utilized by course designers when developing the materials for their course. It is expected that the knowledge of moves and lexico-gramamtical features can help engineering students and novice engineers practice writing the minutes of meetings effectively.